Long-term Care System for Elderly Dependency: Provider Perspectives - ปานันท์ ชัยยา; สุนทราวิรัตน์ บุญมา (Journal of Health Science of Thailand, 2021)
The long-term care service for elderly dependency in Thailand is currently at the early stage of operation. The service system has been developed on the area-based basis. The objective of this study were to assess provider perspectives and develop long-term care system for the dependent elderly. Data were collected by interview of key informants during October 2020 to March 2021, and were analyzed by descriptive and inferential statistics including one way ANOVA (Tukey’s HSD) and Kruskal-Wallis test. There were 384 participants who were divided into three groups: (1) management and local government organization groups, 156 of them, (2) care manager and caregiver groups (157 persons), and (3) operational support groups (71 persons). It was found that there were statistically significant differences among the 3 groups (F=10.349, p<0.001). Comparing the age of the service providers using Kruskal-Wallis Test, statistically significant difference was also observed among the three groups (Chisquare=49.721, p<0.001). The providers had different organizational management perspective due to the difference of their position and age. The provider perspectives were focus on home health services, support for medicine and medical supplies, human resource development, financial regulation process, and procurement. All constraints relating to such perspetives should be seriously addressed in order to strengthen the long-term care services for the dependent elderly.